HUBUNGAN NORMA SUBJEKTIF DENGAN KEYAKINAN UNTUK DETEKSI DINI KANKER SERVIKS METODE IVA - Azzahra, Thasa; Utami, Sri; Erika, Erika (Coping: Community of Publishing in Nursing; Vol 10 No 5 (2022): Oktober 2022, 2022)
Some people have a trend to follow other people's views about their behavior. The people’s views about this action will affect them to belief in early detection of cervical cancer using IVA test. This research is descriptive correlation research using cross sectional approach. The sample in this study were productive women at Rejosari Public Health Center in the amount of 60 respondents based on inclusion criteria using purposive sampling technique. Data collection was conducted by using questionnaire. The questionnaire in this study was the adoption of the questionnaire contained in Theory of Planned Behavior and Health Behavior which had been tested for validity and reliability. The analysis used is univariate analysis and bivariate analysis with the chi square test. The results of this study indicate that the majority of respondents have high subjective norms with high confidence as much as 63,3%, respondents who have low subjective norms with high confidence are 3,3%, and respondents have low subjective norms with low beliefs are 33,3 %. The results of the statistical test obtained p value 0,000 which means there is correlation between subjective norms and the belief in early detection of cervical cancer using the IVA test.